Notarial interaction and the dynamics of agrarian law: approaching complex solutions In transactions and settlement of land disputes - Aslan Noor; Selly Purnama; Shintadewi Dibrata; Indri meliani (Jurnal Info Sains : Informatika dan Sains, 2024)
A notary is a public official who has the authority to make authentic deeds, in addition to other authorities determined by law. At the time UUJN no. 30 of 2004, a debate arose regarding the authority of notaries in making deeds relating to land. The purpose of this research is to find out how effective the role and responsibilities of notaries are as executors of land registration in Indonesia using normative juridical methods by inventorying, reviewing and analyzing and understanding the law as a set of positive norms in the legal system that regulates the role of notaries. This explains that, in the land registration process as stated in PP No. 24 of 1997, that the person who assists the Head of the Land Office is PPAT, notaries are not mentioned as officials who can also help make deeds used for land registration, however there are several deeds which PPAT is not authorized to make so they must use notarial deeds for or as basic land registration. In carrying out land registration activities, the role and responsibility of a notary is very large, this is related to the function of the deed made by the PPAT, namely as proof that a certain legal act has been carried out and as a basis for land registration carried out at the land office. So without a deed made by the PPAT, it will be very difficult to carry out land registration data maintenance activities, because in carrying out land registration activities, the PPAT deed is a binding requirement.